2006
DOI: 10.1063/1.2222370
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative electron attachment to furan, tetrahydrofuran, and fructose

Abstract: We study dissociative electron attachment to furan (FN) (C(4)H(4)O), tetrahydrofuran (THF) (C(4)H(8)O), and fructose (FRU) (C(6)H(12)O(6)) using crossed electron/molecular beams experiments with mass spectrometric detection of the anions. We find that FN and THF are weak electron scavengers and subjected to dissociative electron attachment essentially in the energy range above 5.5 eV via core excited resonances. In striking contrast to that, FRU is very sensitive towards low energy electrons generating a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
94
3
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 42 publications
(41 reference statements)
10
94
3
5
Order By: Relevance
“…ciative electron attachment (DEA) processes. 1,[10][11][12][13][14][15][16][17] However, data on the interaction with electron-donating projectiles, i.e., electron transfer processes in potassium-molecule collisions, are, as far as authors are aware, absent. As such, studying the processes that occur in the context of electron transfer in atom-molecule collisions can be a stepping stone in our understanding of some of the molecular mechanisms that can happen in non-gas-phase environments.…”
Section: Introductionmentioning
confidence: 99%
“…ciative electron attachment (DEA) processes. 1,[10][11][12][13][14][15][16][17] However, data on the interaction with electron-donating projectiles, i.e., electron transfer processes in potassium-molecule collisions, are, as far as authors are aware, absent. As such, studying the processes that occur in the context of electron transfer in atom-molecule collisions can be a stepping stone in our understanding of some of the molecular mechanisms that can happen in non-gas-phase environments.…”
Section: Introductionmentioning
confidence: 99%
“…The condensed phase work was complemented by gas phase DEA fragmentation studies performed by Sulzer et al 7 Of particular importance is the quantitative study of Aflatooni et al 8 who found two DEA bands, at 6.2 and 8 eV, with a surprisingly small cross section, 1.5 pm 2 , about a factor 30 less than that in the 3-hydroxy substituted THF.…”
Section: Introductionmentioning
confidence: 99%
“…Condensedphase experiments on thymidine and a single-strand oligonucleotide have demonstrated that slow electrons do indeed break the C-O phosphate-sugar bonds as well as the C-N base-sugar bonds, [60][61][62] and C-O bond breaking was also found in gas-phase DA to a model phosphodiester. 63 A few electron-collision studies, experimental and theoretical, have looked at the individual backbone constituents, i.e., ribose or deoxyribose and a phosphate group, [64][65][66][67][68][69] and others have also been made of electron collisions with backbone analogs such as tetrahydrofuran, 29,65,[68][69][70][71][72][73][74][75][76][77][78][79] tetrahydrofurfuryl alcohol, 71,72,80,81 fructose, 79 and dibutyl phosphate. 63 However, the only electron collision measurements involving nucleosides that we are aware of are the study by Zheng et al of thymine desorption from condensed-phase deoxythymidine 60 mentioned earlier, and the gas-phase studies by Abdoul-Carime et al 82 and by Denifl et al 83 of DA to deoxythymidine and 5-bromouridine, respectively.…”
Section: Introductionmentioning
confidence: 99%